Automatic Toll Collection System (ATCS) - Israni, Rajiv; Tichkule, Damini; Gopchandani, Bhavna (International Journal of Computer Sciences and Engineering, 2025)
A automatic toll collection systems have really helped a lot in reducing the heavy congestion caused in the metropolitan cities of today. It is one of the easiest methods used to organize the heavy flow of traffic. The system thus installed is quite expedient reducing the time and cost of the travelers. An automatic toll collection system is an advanced system. It is based on IOT and is fully automated. The system will use a raspberry pi board to control the hardware. Toll collection is considered as a hectic task. The collection of toll is a tedious as well as big task to do. The toll amount is to be paid by users manually. To do it in an easy way automatic toll collection system is introduced. This system will make the task of toll collection easy. The payment of toll will be done online with the ease of users. And when the vehicle will approach the toll center the camera will capture license plate and the amount will be deducted direct from user’s account. Through this approach the system will be fully automated.